Pergumulan Rule of Law dan Politik Kapitalisme dalam Konteks Keindonesian - Zaenurrosyid, Ahmad (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2016)
Law, economic have one vision, happiness for human being. We found the existence of inequality in the dynamic economy of Indonesia. This is a crucial problem for sosio-economy productivity. In this writing, Marxism theory about the class and conflict is applied to analyze in Indonesia context. Neo-liberlisme become an ideology of capitalist as legitimation supported by international institution, such as World Bank, IMF,etc. Rule of law in term of dynamic regulation in Indonesia is as a part of alternative solution to control a socio-economic equality supported by progresif law in contemporary era.